(untitled) (Eurasian Journal of Learning and Academic Teaching, 2026)
Foreign Language Speaking Anxiety (FLSA) continues to impede oral fluency of the learner as well. Typically, language instruction includes a number of repetitive drills to improve pronunciation. However, the present study investigates the Social-Emotional Learning (SEL) component of Self-Awareness to enable learners to identify physical and cognitive triggers of their anxiety. The purpose and intent of this research project is to explore the roles of reflective practice and emotional monitoring in alleviating the "fear of negative evaluation" through self-awareness. The preliminary findings of this research indicate that students who utilize self-awareness will be more resilient and exhibit a greater willingness to communicate (WTC) in the classroom.